Posture, blood velocity in common femoral vein, and prophylaxis of venous thromboembolism - Ashby E.C. (1995)
We thank Dr G Comstock and Dr Karen Bandeen-Roche for advice on the paper; Dr C Sanchez, Ms J B Phu, Ms D Sara, and Ms Atenas for technical support; the community of Las Pampas de San Juan for their cooperation; and Mr Patrick Heagerty for computer software. The study was supported by CONCYTEC, Peru, and the RG-ER fund.